The history of the Oxford challenge to marginalism, 1934-1952 - LEE, F.S. (PSL Quarterly Review, 2013)
Economist Hubert Henderson founded Oxford University's Economics Research Group (OERG). The OERG had a history of contesting neoclassical cost and pricing theory as articulated by P.W.S. Andrews, beginning when Hubert Henderson started relying on experiments instead of established data. Henderson and the OERG members were surprised that businessmen disregarded the marginalist model of pricing. Marginalism remains a valid economic theory to this day. JEL: B20